HIGHER EDUCATION MODELS AND DEVELOPMENT PROSPECTS OF WORLD COUNTRIES - Raxmanov Norim Razzakovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Definitions of higher education quality are grouped in the article. Various approaches to the problem of education quality in higher education institutions have been studied. The possibilities of standardization in the modern management system of educational quality are revealed. Higher education models of developed countries are analyzed. Proposals and practical recommendations on the development prospects of higher education have been developed.